2013
DOI: 10.1158/1078-0432.ccr-12-3726
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Redox Activity as a Hallmark of Carcinogenesis: From Early to Terminal Stages of Cancer

Abstract: Purpose: The study aimed to clarify the dynamics of tissue redox activity (TRA) in cancer progression and assess the importance of this parameter for therapeutic strategies.Experimental Design: The experiments were carried out on brain tissues of neuroblastoma-bearing, glioma-bearing, and healthy mice. TRA was visualized in vivo by nitroxide-enhanced MRI on anesthetized animals or in vitro by electron paramagnetic resonance spectroscopy on isolated tissue specimens. Two biochemical parameters were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 45 publications
0
60
0
Order By: Relevance
“…Our data imply that, while the reactions of MnP are likely identical, the magnitude and the end results of such reactions may be profoundly different in normal versus cancer cells, as much as in one versus another cancer cell type. Based on our present understanding, the resulting effects of electron shuttling by MnPs may be prooxidative rather than antioxidative, and particularly so in cancer cells that are already under the conditions of increased oxidative stress (16). The modes of action, other than antioxidative, have also been speculated for Mn salens (229) and polyphenols, and discussed by Forman et al for natural compunds commonly viewed as antioxidants (16,107,108,260).…”
Section: Fig 15 the Anticancer Action Of Mnp As A Sole Agent Anticmentioning
confidence: 74%
See 1 more Smart Citation
“…Our data imply that, while the reactions of MnP are likely identical, the magnitude and the end results of such reactions may be profoundly different in normal versus cancer cells, as much as in one versus another cancer cell type. Based on our present understanding, the resulting effects of electron shuttling by MnPs may be prooxidative rather than antioxidative, and particularly so in cancer cells that are already under the conditions of increased oxidative stress (16). The modes of action, other than antioxidative, have also been speculated for Mn salens (229) and polyphenols, and discussed by Forman et al for natural compunds commonly viewed as antioxidants (16,107,108,260).…”
Section: Fig 15 the Anticancer Action Of Mnp As A Sole Agent Anticmentioning
confidence: 74%
“…Thus, potent SOD mimics are potent peroxynitrite scavengers (Eqs. [15] and [16] P production, can only bear antioxidative character if the cell has either sufficient peroxide-removing enzymes or reductants to eliminate strong oxidants (high valent metal), respectively. If not, as is often the case with oxidative stress injuries and in a particular cancer, the pro-oxidative action may prevail.…”
Section: Drug Reactivitymentioning
confidence: 99%
“…For example, nitroxides as mito-TEMPO and mito-carboxy-PROXYL are mitochondria-targeted derivatives of TEMPOL and carboxy-PROXYL, which currently are widely used as redox-sensors for detection of abnormal superoxide generation in living cells and tissues (2,28,37,(88)(89)(90)(91).…”
Section: Nitroxides As Redox Sensors For Detection Of Mitochondrial Dmentioning
confidence: 99%
“…In vitro studies have demonstrated that various reducers or oxidizers may convert the contrast form of nitroxide radical to non-contrast hydroxylamine, which depends on physiological conditions (2,28,91,93). Figure 5 shows the transformations between the oxidation radical state of nitroxide, hydroxylamine, and oxoammonium states.…”
Section: Nitroxides As Redox Sensors For Detection Of Mitochondrial Dmentioning
confidence: 99%
See 1 more Smart Citation